Commercialisation des produits de beauté, pratiques esthétiques et représentations du corps de la femme à Montréal, 1870-1915 - Chartrand, Mélanie (Université de Montréal, 2004)
Keywords: Femmes; Publicité

La femme illustrée par Dupuis frères limitée - de Andrade, Marie-Maxime (Cap-aux-Diamants, 2018)
Keywords: Dupuis Frères; Femmes; Magasins

N’être plus la déléguée de personne: une réévaluation du rôle des femmes dans le commerce en Nouvelle-France - Noel, Jan (Revue d'histoire de l'Amérique française, 2009)
Keywords: Femmes; Fourrure; Marchands

Mobilité et accessibilité aux services et aux transports des femmes âgées à Montréal - Murat, Chesena (Université de Montréal, 2006)
Keywords: Automobile; Femmes; Transport en commun

"S'unir pour être plus fort": le Conseil des femmes membres de la Chambre de commerce du district de Montréal, 1956-1971 - Detellier, Élise (Université de Montréal, 2004)
Keywords: Chambre de commerce; Femmes

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Le travail des femmes célibataires de l'élite et la famille pendant la période préindustrielle à Montréal - Fortin, Jonathan (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Keywords: Famille; Femmes; Fourrure; Marchands; Travail

Louise Paradis: une femme à la tête du domaine Saint-Gabriel des Sulpiciens - Blondin, Yves (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Baux à ferme; Communautés religieuses; Famille; Femmes; Saint-Gabriel (ferme); Sulpiciens

Pour les femmes, par les femmes : une histoire entrepreneuriale de la presse féminine québécoise au tournant du XXe siècle - Rocher-Lewis, Delphine (Université du Québec à Montréal, 2021)
Keywords: Barry, Robertine; Bélanger, Georgina (De Montreuil, Gaétane / Bélanger, Georgine); Femmes; Journalistes; Marchand-Dandurand, Joséphine

Berthe Chaurès-Louard, une femme engagée qui a laissé des traces dans notre communauté - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Alimentation; Chaurès-Louard, Berthe; La Familiale

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

"Due Attention Has Been Paid to All Rules": Women, Tavern Licences, and Social Regulation in Montreal, 1840–1860 - Poutanen, Mary Anne (Histoire sociale / Social History, 2017)
Keywords: Femmes

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

Représentations des immigrantes roumaines sur leurs usages d'internet en contexte d'immigration à Montréal - Regus, Oriane (Université du Québec à Montréal, 2008)
Keywords: Femmes; Internet; Roumains

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
Keywords: Eaton; Femmes; Magasins

La contrebande à Montréal, 1729-1752: passages, pratiques et protagonistes - Robert, Dhyana (Université de Sherbrooke, 2016)
Keywords: Criminalité; Femmes; Marchands

Shelter from the Hurry? Hospitality in Montreal, 1836-1913 - Poutanen, Mary Anne; Olson, Sherry (Architectures of Hurry - Mobilities and Modernity in Urban Environments, 2018)
Keywords: Auberges; Femmes; Hôtellerie

Les conditions et les " scènes " de visibilité médiatique lesbienne et féministe: l’atelier de photographie Plessisgraphe des années 70 et 80 - Pidduck, Julianne (Recherches féministes, 2020)
Keywords: Femmes; Féminisme; Photographie

One (Wo)man’s Shopping is the Same (Wo)man’s history? Immigration, Advertisement and Consumption Patterns in the Greek community of Montreal 1960s-1970s - Pabst, Stavroula (Études canadiennes / Canadian Studies, 2009)
Keywords: Femmes; Grecs; Publicité

"Every Attention Will Be Paid to the Satisfaction of the Guests": Angélique Archambault and Donegana’s Hotel, 1852-1864 - Poutanen, Mary Anne (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Femmes; Hôtellerie; Mariage

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Université Concordia, 2020)
Keywords: Femmes; Grèves; Textile

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

La naissance du quartier de la Poudrière (1) - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Armes; Femmes; Guerre; Verdun

Through the Mill: Girls and Women in the Quebec Cotton Textile Industry, 1881-1951 - Cuthbert Brandt, Gail (Baraka Books, 2018)
Keywords: Femmes; Grèves; Textile; Travail

Public Houses and Hidden Networks: Roles of Women in Mid-Nineteenth-Century Montreal - Poutanen, Mary Anne; Olson, Sherry (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Auberges; Famille; Femmes; Hôtellerie

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Gender and Social Relations in the City above the Hill - Sweeny, Robert C.H. (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Quartiers

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

“La Grève de la fierté”: Resisting Deindustrialization in Montréal’s Garment Industry, 1977–1983 - Laframboise, Lauren (Labour / Le Travail, 2023)
Keywords: Femmes; Grèves; International Ladies' Garment Workers' Union; Vêtements

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

"Hotel Refuses Negro Nurse": Gloria Clarke Baylis and the Queen Elizabeth Hotel - Flynn, Karen (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2018)
Keywords: Femmes; Hôtellerie; Infirmières; Noirs; Reine-Élizabeth (hôtel)

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d'histoire de l'Amérique française, 2022)
Keywords: Femmes; Montreal Light, Heat and Power; Travail; École ménagère; Électricité

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

Les défis de la sauvegarde du patrimoine à la Société d'histoire d'Ahuntsic-Cartierville - Labarussias, Jordane (Histoire Québec, 2018)
Keywords: Ahuntsic; Armes; Cartierville; Conservation; Femmes; Forts; Guerre; Histoire; Patrimoine; Quartiers; Sault-au-Récollet

Des exceptions qui confirment les règles? L'entrepreneuriat féminin à Montréal, 1920-1980 - Gallez, Philomène (Université de Montréal, 2017)
Keywords: Chambre de commerce; Commerce de détail; Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Board of Trade; École des hautes études commerciales

Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle) - Guay, Élyse; Nadon, Rachel (Nouvelles études québécoises, 2021)
Keywords: Cité Libre; Dérives (revue); Femmes; Fugues (revue); Féminisme; Humour; Les Têtes de Pioche (journal); Nationalisme; Parti Pris; Patrimoine; Traduction

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde, Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

Tourner à droite, virer à gauche. Le Plateau politique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
Keywords: Beaubien, Louis; Bethune, Norman; Chemins de fer; Communistes; Confection; Conseillers municipaux; Députés; Femmes; Gares; Grèves; Juifs; Mile End; Médecine; Partis politiques; Plateau Mont-Royal; Quartiers; Rose, Fred; Syndicats internationaux; Travail; Union internationale des ouvriers du vêtement pour dames; Élections